2005
DOI: 10.1111/j.1442-2042.2005.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand‐assisted laparoscopic and open living donor nephrectomy in Korea

Abstract: Results : There was one conversion to an open procedure due to bleeding in the LLDN group. The median operation times (180 min in LLDN versus 170 min in OLDN) and warm ischemic times (2.5 min in LLDN versus 2.0 min in OLDN) in the two groups were similar. The estimated mean blood loss, duration of hospital stay and complication rate was also similar in the two groups. The LLDN group reported less pain (visual analog scale) postoperatively (4.1 versus 5.3), but this was not significant ( P = 0.058). The time to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although the laparoscopic approach has become widely used, 1 3 open nephrectomy is still recommended and widely performed because of the difficulty, longer ischaemic time and higher incidence of ureteral complications associated with the minimally-invasive approach. 4 The extraperitoneal loin incision for open nephrectomy can cause severe postoperative pain that may decrease quality of life. 3 A multimodal approach has been attempted to accomplish effective pain control during the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Although the laparoscopic approach has become widely used, 1 3 open nephrectomy is still recommended and widely performed because of the difficulty, longer ischaemic time and higher incidence of ureteral complications associated with the minimally-invasive approach. 4 The extraperitoneal loin incision for open nephrectomy can cause severe postoperative pain that may decrease quality of life. 3 A multimodal approach has been attempted to accomplish effective pain control during the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis presented that laparoscopic donor nephrectomy (LDN) has been associated with fewer complications, shorter LOS, and faster return to work than those with ODN [ 14 , 15 ]. Our center also reported in a previous comparison study that LDN may have the ability to provide grafts of similar quality to ODN [ 16 ].…”
Section: Discussionmentioning
confidence: 57%
“…In a study, the stay time of the donors with the laparoscopic nephrectomy and open nephrectomy has reported as comparable [16]. A study has shown that some other studies as underreport and underestimate about the laparoscopic donor nephrectomy results also morbidity and mortality with laparoscopic donor nephrectomy have been reported and also long time training is necessary to be comfortable at doing the laparoscopic donor nephrectomy has been reported [17].…”
Section: Journal Of Transplantation Technologies and Researchmentioning
confidence: 99%
“…A study has reported a size of incision in the open donor nephrectomy may be comparable with the size of incision at the laparoscopy donor nephrectomy [18]. With regarding all of the mentioned above, it may be advised if laparoscopy donor nephrectomy is not possible at some centers, it is possible with having more experience about open donor nephrectomy to do open donor nephrectomy with results comparable with laparoscopic donor nephrectomy [16][17][18].…”
Section: Journal Of Transplantation Technologies and Researchmentioning
confidence: 99%